Recent Dermatological Treatments for Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis in Japan - Hsieh, Ming-Hsiu; Watanabe, Tomoya; Aihara, Michiko (Frontiers in Medicine, 2021)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are serious conditions characterized by necrosis of the skin and mucus membranes, and are mainly caused by medication and infections. Although the exact pathomechanism of SJS/TEN remains unclear, keratinocyte death is thought to be triggered by immune reactions to these antigens. While there is no established therapy for SJS/TEN, corticosteroids and intravenous immunoglobulin (IVIG) have been utilized as immunomodulator. We previously conducted a study to evaluate the efficacy of IVIG therapy in Japanese patients with SJS/TEN. IVIG was administered at a dosage of 400 mg/kg/day for 5 consecutive days as an additional therapy with systemic steroids. Prompt amelioration was observed in seven of the eight patients. All patients survived without sequelae. Recently, we retrospectively analyzed 132 cases of SJS/TEN treated in our two hospitals. The mortality rates in the patients treated with methylprednisolone pulse were 0% (0/31) for SJS and 7.0% (3/43) for TEN, and 0% (0/10) in the TEN patients treated with methylprednisolone pulse in combination with IVIG. These results suggest that early treatment with high-dose steroids, including methylprednisolone pulse therapy, and IVIG together with corticosteroids are possible therapeutic options to improve the prognosis of SJS/TEN.